2014
DOI: 10.1080/09593330.2014.896951
|View full text |Cite
|
Sign up to set email alerts
|

Microbial desalination cell for enhanced biodegradation of waste engine oil using a novel bacterial strainBacillus subtilis moh3

Abstract: Microbial desalination cell (MDC) is a bioelectrochemical system developed recently from microbial fuel cells (MFCs), for producing green energy from organic wastes along with desalination of saltwater. MDC is proved to be a better performer than MFC in terms of power output and chemical oxygen demand removal, with desalination as an additional feature. This study investigates the application potential of MDC for integrated biodegradation of waste engine oil. This study showed, for the first time, that waste e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The removal of PAHs is generally high in liquid media, often reaching 100 % when a minimal media (Adelaja et al, 2015(Adelaja et al, , 2014 were used. It varied between 55 and 82 % for PAH-containing liquids such as real-field petrochemical wastewater (Yeruva et al, 2015), waste engine oil from saline water (Sabina et al, 2014) or diesel-contaminated media (Morris et al, 2009). In wastewater, the highest removal rate of an aromatic fraction in MFC in aqueous media reached 70 % within 17 days with an initial load of 3 g TPH/L.…”
Section: Differences In the Performances Of Pah-degrading Mfcs In Sol...mentioning
confidence: 99%
See 1 more Smart Citation
“…The removal of PAHs is generally high in liquid media, often reaching 100 % when a minimal media (Adelaja et al, 2015(Adelaja et al, , 2014 were used. It varied between 55 and 82 % for PAH-containing liquids such as real-field petrochemical wastewater (Yeruva et al, 2015), waste engine oil from saline water (Sabina et al, 2014) or diesel-contaminated media (Morris et al, 2009). In wastewater, the highest removal rate of an aromatic fraction in MFC in aqueous media reached 70 % within 17 days with an initial load of 3 g TPH/L.…”
Section: Differences In the Performances Of Pah-degrading Mfcs In Sol...mentioning
confidence: 99%
“…Optimum conditions for soil MFCs included a 1 % salt content (w/v) for which 91.6 % and 79.1 % of hydrocarbons and COD, respectively, were removed, with a maximum power density of 1.06 mW/m 2 (Adelaja et al, 2015). Furthermore, waste engine oil was used as an organic substrate in a desalination microbial fuel cell that achieved biodegradation of branched and cyclic aliphatic hydrocarbons (70.1 ± 0.5 %) along with desalination (68.3 %) and power production (3.1 mW/m 2 ) (Sabina et al, 2014). In consequence, 8 % more hydrocarbon was removed than when preliminary flask studies were carried out with the same Bacillus subtilis moh3 culture isolated from waste engine oil.…”
Section: Salinitymentioning
confidence: 99%
“…In addition to that, mathematical modelling integrated UV-Vis spectroscopy has effectively deduced the substrate utilization process, microbial activity products, and biomass-associated products as indicators of various samples(209).An interesting study developed a microbial desalination cell from a novel bacterial strainBacillus subtilis moh3 which was used for integrated biodegradation of waste engine oil. GC-MS analysis showed 70.1±0.5% biodegradation and also indicated the cleavage of long chain, branched and cyclic hydrocarbons present in the waste engine oil(210). A study by Louvet et al(211) illustrated the slaughterhouse wastewater treatment by the use of activated sludge confirmed by UV-Visible absorbance and fluorescence spectroscopy.…”
mentioning
confidence: 96%
“…Sabina et al [87] recently demonstrated a novel application of MFC principle with huge future prospects. The team developed a microbial desalination cell in which Bacillus subtilis degraded waste engine oil with considerable power production (3.1 ± 0.3 mW/m 2 ) along with desalination and enhanced biodegradation.…”
Section: Materials Advancesmentioning
confidence: 99%